PETROGENESIS OF CARBONATITE MAGMAS FROM MANTLE TO CRUST, CONSTRAINED BY THE SYSTEM CAO-(MGO + FEO*)-(NA2O + K2O)-(SIO2 + AL2O3 + TIO2)-CO2 - Lee W.J.; Wyllie P.J. (My University, 1998)
Experimental results from the systems CaO-MgO-SiO2-CO2, Na2O-CaO-Al2O3-SiO2-CO2, and a primitive magnesian nephelinite mixed with carbonates have been combined for construction of phase diagrams for the pseudoquaternary system CaO-(MgO + FeO*)-(Na2O + K2O)-(SiO2 + Al2O3 + TiO2) with CO2 at 1·0 and 2·5 GPa pressure. These diagrams provide a petrogenetic framework for magmatic processes from mantle to deep crust, with particular reference to the melting products of carbonate peridotite and the paths of crystallization of carbonated silicate magmas toward carbonatite magmas, with or without the intervention of silicate-carbonate liquid immiscibility. Three key features control these processes: (1) the liquidus surface bounding the silicate-carbonate liquid miscibility gap, (2) the silicate-carbonate liquidus boundary surface which separates the liquidus volume for primary silicates from that for primary carbonates, and (3) the curve of intersection of these two surfaces (1 and 2) which defines the coprecipitation of silicates and calcite with coexisting immiscible silicate- and carbonate-rich liquids. The geometrical arrangement of the two surfaces varies as a function of both pressure and bulk composition (e.g. with Si/Al, Na/K, Mg/Fe). Surface (2) is the locus of initial liquids from partial melting of carbonate-silicate assemblages, and the limit for residual liquid compositions derived from silicate-CO2 liquids. The carbonate liquidus volume is a forbidden region for carbonate-rich magmas derived from silicate magmas at the pressures investigated. The immiscible liquids dissolve no more than 80 wt % CaCO3, and the miscibility gap (MG) becomes smaller with increasing Mg/Ca. Extrapolation of experimental data indicates that the MG disappears with more than ~50 wt % (MgO + FeO*) at 1·0 GPa for the compositions investigated. The distance between the miscibility gap, surface (1), and the silicate-carbonate liquidus surface, surface (2), increases significantly with increasing (MgO + FeO*). This observation, coupled with knowledge of the phase boundaries in the system, allows comparisons with projected rock compositions, and this permits the following conclusions. Calciocarbonatites and natrocarbonatites are excluded as candidates for primary magmas from the mantle, which must have compositions dominated by calcic dolomite. The formation of (equilibrium) carbonate-rich liquids immiscible with silicate magmas in the mantle is unlikely, which denies the formation of CaCO3 ocelli in mantle xenoliths as immiscible liquids. Immiscible carbonate-rich magmas separated from many silicate magmas may tend to be concentrated near calciocarbonatite compositions, with maximum CaCO3 75-80 wt %, low (MgO + FeO*), and (Na,K)2CO3 near 15 wt %. Silicate parents with higher Na/Ca and peralkalinity may yield immiscible magmas approaching natrocarbonatite compositions. Exsolution of immiscible carbonate-rich magma occurs without the coprecipitation of calcite except along the limiting field boundary (3). Only after the carbonate-rich magma is physically separated from the parent magma, and cooled with the precipitation of silicates, does it reach the silicate-carbonate field boundary and precipitate cumulate carbonatites, with inevitable enrichment of residual liquids in alkalis. Calciocarbonatite magmas cannot be derived from natrocarbonatite magmas. Dolomitic carbonatite magmas cannot be formed by liquid immiscibility, but only by fractionation of calciocarbonatites (according to CaCO3-MgCO3), or as primary magmas.
Keywords: CaCO3 ocelli; carbonatite; liquid immiscibility; nephelinite